Discipline in the secondary classroom : a problem-by-problem survival guide - Sprick, Randall S. (West Nyack, N.Y. : Center for Applied Research in Education, 1985)
Preparation and organization. Self-discipline and motivation. Consequences for misbehavior. Troubleshooting specific problems.
Keywords: Classroom management; High school students; Discipline; Problem children; High school students -- Discipline; Problem children -- Discipline; Classroom management